KONGLISH BORROWING TRANSLATION IN KOREAN “SWEET & SOUR” MOVIE - Rita Hartati; Stevany Silaban; Wildina Theressa (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2023)
Konglish is a Korean vocabulary adapted from English but pronounced according to Korean pronunciation. The pronunciation usually seems to sound like Korean, but the writing is more towards spelled English. An example is "Big Size" which in Korean becomes 빅 사이즈 (bik-sa-ee-jeu). This analysis focuses on Konglish findings in the Korean film that aired on 2021 entitled Sweet & Sour. "Sweet and Sour" is a captivating romantic comedy-drama film from South Korea, helmed by director Lee Gye-byeok. The purpose of this study is to analyse the various word formation Konglish found in Sweet & Sour films and classify them according to the borrowing characteristics theory from Molina & Albir (2002). The researcher alson want to know the reason behind why the dominant type of Konglish borrowing are found. Molina & Albir (2002) have classified borrowing more detail into two characteristics: (1) pure borrowing, and (2) naturalized borrowing. This research uses the descriptive qualitative method because the results of the analysis presented descriptively. The data analysis technique used is to rewrite the dialogue in the form of a transcript, then take note and analyse the Konglish words contained in the dialogue. The results of this research found around 42 Konglish found in the film "Sweet and Sour" with details: Naturalized Borrowing found 13 times with a percentage of 30.95%. and Pure Borrowing found 29 times with a percentage of 69.04% and the influence of working field as this movie’s background made Pure Borrowing as the dominant type found.Keyword: Borrowing word, Konglish, Naturalized, Pure